SEROPREVALENCIA DE Neospora caninum EN BOVINOS LECHEROS DE CUATRO DISTRITOS DEL VALLE DEL MANTARO, JUNÍN. - Granados Z., Silvia (2014)
The aim of this study was to determine the frequency of N. caninum in dairy cows inthe Mantaro valley, Junin, Peru. A total of 182 female cattle sera from 15 dairy farms of thedistricts of Matahuasi, Concepción, 9 de Julio and Santa Rosa were analyzed by theIndirect ELISA test using a commercial kit to determine antibodies against N. caninum.The seroprevalence was 46.7 ± 7.2% (85/182). The districts of Matahuasi and Santa Rosashowed the highest 68.7% and lowest (17.8%) seroprevalence respectively. The resultsconfirm the presence of a relatively high frequency of N. caninum in dairy cattle of theMantaro valley.